2021
DOI: 10.1097/nmd.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Anxiety Disorder During the COVID-19 Outbreak in Iran

Abstract: The COVID-19 epidemic has both physical and psychosocial consequences for the general population. The present study aimed to investigate the relationship between the prevalence of generalized anxiety disorder (GAD) and social dysfunction during the COVID-19 epidemic in Iran. This cross-sectional web-based study was conducted on 1000 Rafsanjani citizens in southeastern Iran. Data were collected by using the Generalized Anxiety Disorder-7 and the General Health Questionnaire from March 15 to March 30, 2020. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Moreover, anxiety levels closely mirrored the daily number of new cases during the 2003 outbreak of severe acute respiratory syndrome in Hong Kong [12]. Recent studies showed that substantial proportions of the general population reported moderate-to-severe symptoms of anxiety during the initial outbreak of COVID-19 in Iran (28%) [13], China (29%) [14], the United Kingdom (24%) [15], Canada (20%) [16], Belgium (15%) [16], Switzerland (12%) [16], the Philippines (23%) [16], and Bangladesh (37%) [17]. The percentages of moderate-to-severe anxiety in China and the UK were lower before the COVID-19 pandemic [18,19].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, anxiety levels closely mirrored the daily number of new cases during the 2003 outbreak of severe acute respiratory syndrome in Hong Kong [12]. Recent studies showed that substantial proportions of the general population reported moderate-to-severe symptoms of anxiety during the initial outbreak of COVID-19 in Iran (28%) [13], China (29%) [14], the United Kingdom (24%) [15], Canada (20%) [16], Belgium (15%) [16], Switzerland (12%) [16], the Philippines (23%) [16], and Bangladesh (37%) [17]. The percentages of moderate-to-severe anxiety in China and the UK were lower before the COVID-19 pandemic [18,19].…”
Section: Introductionmentioning
confidence: 84%
“…Items are summed, resulting in a total score ranging from 0 to 21, with higher scores indicating higher levels of anxiety. Based on the total score, 4 levels of anxiety severity were derived: minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (5-21) [43]. As a screening instrument for GAD symptoms, a GAD-7 score of 10 or greater has been proposed, yielding a sensitivity of 89% and a specificity of 82% for GAD [43].…”
Section: Measures 221 Outcome: Generalized Anxiety Disorder Symptomsmentioning
confidence: 99%
“…On March 11, 2020, the World Health Organization declared COVID-19 a pandemic ( Sahin et al, 2020 ). Certainly, the general public has experienced anxiety, stress, fear, uncertainty, and insecurity as a result of the COVID-19 pandemic ( Zakeri et al, 2021c , f ). In this dire situation, nursing is one of the most important occupational groups, as well as one of the foundations of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the general public has experienced anxiety, stress, fear, uncertainty, and insecurity as a result of the COVID‐19 pandemic (Zakeri, Hosseini Rafsanjanipoor, Kahnooji, et al, 2021 ; Zakeri, Hosseini Rafsanjanipoor, Sedri, et al, 2021 ). Studies have shown that in times of crisis, particularly infectious crises, psychological responses such as anxiety, depression, stress, and fear can have a negative impact on people's health (Pappas et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%